A cross-sectional survey of parental perceptions of COVID-19 related hygiene measures within schools and adherence to social distancing in journeys to and from school. Issue 1 (9th September 2020) - Smith, Louise E; Woodland, Lisa; Amlôt, Richard; Rubin, Antonia; Rubin, G James
Abstract : During the early stages of the COVID-19 pandemic, schools in England were only kept open to children of 'key workers' and, from 1 June, to children in reception, year 1 and year 6. Our cross-sectional survey of parents found low rates of attendance (<50%) in both groups. Many parents whose children attended school reported low adherence to hygiene measures (eg, not maintaining distance from others during school drop-off) and doubted that their school was adhering to COVID-19 guidelines. This must be improved if parents are to feel confident about a more comprehensive return to school, as planned for September.